Modos de pensamento de adultos em processo de escolarização na EJA - Ana Catharina Mesquita de Noronha (2013)
This work aimed to understand adults ways of thinking during the schooling process of YAE (Youth and Adult Education). The methodological approach, founded on the qualitative nature, was chosen. The strategy for investigating was the collective case study. The research was accomplished in an elementary school classroom of YAE (RME/BH: Municipal Educational System of Belo Horizonte). The analyses of the data were oriented around the theoretic and methodological references based upon Historic/Cultural Psychology. One searched how and under which conditions the students have thought of the knowledge they have achieved through the pedagogical practice. Each individual could be recognized as social actors in their histories, marked by poor conditions of life, injustices and social exclusions. These individuals have expressed, by their thoughts, statements, how they have built their knowledge. One could observe that the basis of their thoughts about school learning have been inside their sociocultural lives, pointing out different reading and interpretation possibilities of these knowledge. The case studies revealed that the thought expressed by words was not an isolated construction out of the constitution of the historical and cultural individual.